A CONTRIBUTION TO THE TAXONOMY AND ECOLOGY OF LITTLE-KNOWN INDONESIAN AFISSA LADYBIRD BEETLES (COCCINELLIDAE, EPILACHNINI) - Arif Maulana; Tri Atmowidi; Sih Kahono (BRIN Publishing (Penerbit BRIN), 2020)
We collected the little-known ladybird beetle Afissa incauta in the mountainous region of Bandung, West Java. The beetle occurred sympatrically with the very similar species A. gedeensis. Here, we provide an update to the current knowledge for these two species. The A. incauta we collected have a slightly smaller and duller body compared to the previously known specimens of Afissa incauta, with convergent elytral maculation similar to A. gedeensis.